Sympathetic sideband cooling of a 40Ca+–27Al+ pair toward a quantum logic clock. (24th January 2018) - Cui, Kai-feng; Shang, Jun-juan; Chao, Si-jia; Wang, Shao-mao; Yuan, Jin-bo; Zhang, Ping; Cao, Jian; Shu, Hua-lin; Huang, Xue-ren
Abstract: We achieve the sympathetic sideband cooling of a 40 Ca + – 27 Al + pair. Both axial modes of the two-ion chain are cooled simultaneously to near the ground state of the motion. The center of mass mode is cooled to an average phonon number of 0.052(9), and the breathing mode is cooled to 0.035(6). The heating rates of both a single 40 Ca + and the 40 Ca + – 27 Al + pair are measured and compared. This work is a fundamental step toward the implementation of a 40 Ca + – 27 Al + quantum logic clock.